Juridicial Review of The Role of Indonesian Army in The Government Governance System - Raihan Putra Sakha; Dodi Jaya Wardana (Law Development Journal, 2025)
This study aims to determine the contents of the TNI Bill, which contains regulations governing the duties and authorities of the TNI. The TNI Bill regulates active TNI soldiers assigned as the Indonesian National Armed Forces, thus determining the roles that may and may not be performed within government institutions. The amendment to the TNI Bill was first proposed by the Indonesian House of Representatives (DPR RI) to provide a more detailed legal basis for the TNI's role in carrying out national defense duties. However, the amendment to the TNI Bill has raised public concern, as it is feared that the amendment to the TNI Bill will replace the previously civilian-led government with active TNI members, potentially leading to a repeat of the events of the New Order era, in which most state governments were staffed by ABRI personnel, which in practice severely limited freedom of expression. This study aims to determine the duties of governance, and the impact is also to determine the strengths and weaknesses of state institutions or ministries that will be staffed by Indonesian National Armed Forces soldiers in accordance with the approved bill. Meanwhile, the research used is normative juridical research (legal research). While legal research (legal research) according to Peter Mahmud Marzuki is to find a coherent truth, namely whether there are legal rules in accordance with legal norms and whether there are norms in the form of commands or prohibitions that are in accordance with legal principles and whether actions (acts) a person in accordance with legal norms (not just legal rules) or legal principles.